Medieval women - Power, Eileen (Cambridge University Press, 1997)
Throughout her career as a medieval historian, Eileen Power was engaged on a book on women in the Middle Ages. She did not live to write the book but some of the material she collected found its way into her popular lectures on medieval women. These lectures are now brought together, edited by M. M. Postan, and reveal the world in which women lived, were educated, worked, and worshipped. Power gives a vivid account of the worlds of the lady, the peasant, the townswoman, and the nun. The result is a historical yet intimate picture of a period gone by yet with resonances for today. For this edition, Maxine Berg is also included, offering an intimate portrait of the writer and social historian.